2016
DOI: 10.1016/j.biopsych.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

A Spatiotemporal Profile of In Vivo Cerebral Blood Flow Changes Following Intranasal Oxytocin in Humans

Abstract: Our study provides the first visualization and quantification of IN-OT-induced changes in rCBF in the living human brain unaffected by cognitive, affective, or social manipulations. Our findings can inform theoretical and mechanistic models regarding IN-OT effects on typical and atypical social behavior and guide future experiments (e.g., regarding the timing of experimental manipulations).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
165
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(181 citation statements)
references
References 141 publications
14
165
2
Order By: Relevance
“…An anatomical scan was first acquired, followed by an emotional face-matching task, which began on average 44.68 (±3.74) minutes after intranasal spray application. This is in line with previous intranasal fMRI studies (Kirsch et al, 2005;Labuschagne et al, 2010), and coincides with the pharmacodynamic peak response of intranasal OT in healthy individuals (Paloyelis et al, 2014).…”
Section: Methodssupporting
confidence: 92%
“…An anatomical scan was first acquired, followed by an emotional face-matching task, which began on average 44.68 (±3.74) minutes after intranasal spray application. This is in line with previous intranasal fMRI studies (Kirsch et al, 2005;Labuschagne et al, 2010), and coincides with the pharmacodynamic peak response of intranasal OT in healthy individuals (Paloyelis et al, 2014).…”
Section: Methodssupporting
confidence: 92%
“…First, two task-based fMRI scans were conducted: an emotional face-matching task (Koch et al, 2015) and a monetary (Nawijn et al, 2016a) and social (Nawijn et al, 2016b) incentive delay reward task. Hereafter, the resting-state scan was conducted, which began on average 72.51 min (±4.03) after intranasal spray administration, when neuropharmacological OT administration effects on cerebral blood flow (Paloyelis et al, 2014) and elevated OT levels in cerebrospinal fluid (Striepens et al, 2013) are still observed. During resting-state scanning, participants were instructed to relax and let their mind wander, with open eyes.…”
Section: Methodsmentioning
confidence: 99%
“…Neuroimaging studies in humans have shown that intranasal administration of oxytocin, which circumvents issues of peripherally administered hormone crossing the blood brain barrier (Tracy et al, 2015), results in increased regional cerebral blood flow in areas, such as the opercular-insula and anterior cingulate cortex, that are implicated in nociceptive processing and the pain experience (Paloyelis et al, 2016a;Treede et al, 1999).…”
Section: The Analgesic Effects Of Oxytocinmentioning
confidence: 99%